AGGRAVATION OF GENTAMICIN INDUCED NEPHROTOXICITY BY CIPROFLOXACIN: Gentamicin Induced Nephrotoxicity - ., Dr Ambreen Zafar; ., Azhar Mubarik; ., Alia Zubair; ., Shahid Jamal; ., Aiza Saadia (Pakistan Armed Forces Medical Journal, 2013)
Objective: To evaluate histopathological changes of gentamicin induced nephrotoxicity in rabbits receiving the combination of ciprofloxacin and gentamicin compared with rabbits receiving gentamicin alone.Study Design: Laboratory based Randomized controlled trial.Place and Duration of Study: Study was conducted in the department of Histopathology with the collaboration of the department of Pharmacology, Army Medical College Rawalpindi and National University of Sciences and Technology (NUST) Islamabad.Material and Methods: Eighteen rabbits were used in this study. They were divided randomly into three groups. Each group contained six rabbits. Group 1 (control) was injected subcutaneously with 0.9% NaCl. The second group of animals was injected with gentamicin. The third group of animals was injected with the same dose of gentamicin and additionally ciprofloxacin. The findings were entered and analyzed with the help of histopathological (HP) score calculated by summing up the histological parameters through Microsoft excel and Graph pad Instat 3.Results: Necrosis, congestion and inflammatory infiltrate were graded as absent, mild, moderate and severe. The score assigned was from 0 to 4 accordingly. Highest tubular necrosis grade (grade 3) and maximum inflammatory changes (moderate grade) were observed in 50% of rabbits of group 3, receiving combination of gentamicin and ciprofloxacin. p-values were significant